Diversification - Morris, William T. (Management Science, 1958)
The logical structure of diversification as a management policy is discussed through the use of simple examples. For a decision maker who maximizes expectation in the face of uncertain prospects, the kinds of utility functions which lead to the use of diversification are explored. It is shown that conditions of positive but decreasing marginal utility must prevail, and the conditions for optimal diversified programs are given. The use of diversification as a policy for the reduction of variance of outcomes is discussed. For a decision maker whose choices are rationalized in terms of aspiration levels, the situations in which this policy might be used are also explored.